Effect of an Educational Booklet on Knowledge and Attitude Regarding Major Depressive Disorder in Medical Students in Delhi - Medha Goyal; Charu Kohli; Jugal Kishore; Ram C. Jiloha (University Library System, University of Pittsburgh, 2013)
Background: Depression is one of the most common mental disorders affecting people in the world. It is also a growing concern in younger population particularly medical students. There are many pharmaceutical interventions for treatment of depression but there is paucity of data to determine the effect of educational intervention on the knowledge, attitude and help seeking behaviour regarding depression among medical students.  Methods: An interventional study was carried out among randomly selected 100 medical students except interns over a period of 6 months from March August 2011 in a medical college in Delhi to assess the effect of educational booklet on knowledge and attitude about depression. Data was collected using pre-tested questionnaire and analyzed using SPSS version 16 software. Statistical significance in pre and post intervention proportions was determined using Mc Nemar test (MN) and for other proportions Chi-square test.  Results: The study shown that only 71% of subjects knew that depression is a disease in pre intervention phase, which rose to 88% in post intervention phase (p=0.01). Knowledge of symptoms and treatment significantly improved such as trouble falling asleep or too much sleep (p=0.03), feeling tired or decreased energy (MN=17.6, p=0.01), feeling bad about self (MN=21.8, p=0.01), speaking slowly other can notice (MN=19.1, p=0.01) and can be treated by improving awareness (MN=8.6, p=0.03), and anti-depressants do not cause much of side effects (MN=17.3, p=0.01). Most common reasons for not seeking help were thinking that there is lack of understanding by other people about the depression (63%), lack of confidentiality (49%), social stigma (30%), fear of rejection (26%) and time constraints (6%). Majority of students accepted the booklet for their understanding about depression where 63% considered that it improved their knowledge to great extent.  Conclusion:Educational interventional booklet should be promoted at bigger level to help students to identify and understand the depression which may improve health seeking behavior and could decrease their suffering if they fall sick.